General practitioners translating ultrasonography into clinical practice in rural Nepal: rewarding practices and challenges - Dangal, Binod; Poudel, Rajesh; Shrestha, Pradita (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Ultrasound has been increasingly implemented in general practice for its diagnostic and therapeutic purposes. The recent introduction of Point of Care Ultrasound (POCUS) has changed the intended management plans reducing referrals and morbidity and mortality. Inadequate numbers and less availability of radiologists in peripheral setting is a major challenge for coverage of ultrasonography services in remote Nepal. MD General Practitioner (MDGPs) in district hospitals have performed and interpreted large variety of cases for better clinical outcome. Regular communication, coordination and collaboration meeting between MDGPs and radiologists, specific updates and training programs are needed for MDGPs to further strengthen their skills.